Smart Digital Measurement System for Rural Water Quality Monitoring Using IoT - Puteri Nurul Ma'rifah; Puteri Nurul Magfirah; Ekananda Kinanthi Rahayu; Mikail Shauqi; Ihyau Rofiki Sukman R.T.; Safriudin Rifandi (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2025)
Clean water is essential for public health and quality of life. Yet, many rural areas in Indonesia still rely on well water that often has high turbidity, too many dissolved solids, and risks of biological contamination. To help solve these problems, this study created and tested a Smart Digital Measurement System using Internet of Things (IoT) technology to monitor and improve water quality. The system includes a digital monitoring unit with pH, TDS, and turbidity sensors, which send data to the Blynk IoT dashboard and a Telegram bot for notifications. It also uses a multi-stage filtration unit with sedimentation filters, activated carbon, and UV sterilizers. Tests on wells in Gesikan, Tuban, showed the system worked reliably, with an average data transmission delay of 1.72 seconds, sensor errors below 5%, and 99% uptime over seven days. Water quality improved: pH levels rose to nearly neutral (6.8 to 7.0), TDS dropped by more than half (from 520–560 ppm to 240–260 ppm), and turbidity fell by about 75% (from 30–35 NTU to 6–8 NTU). These results show that the system offers an affordable way to help rural communities get cleaner water and supports progress toward SDGs 3 (Good Health and Well-being) and 6 (Clean Water and Sanitation).